Evolution of Female Images in Russian Literature Until 18th Century - qizi, Obidova Farangiz Akmal (European Journal of Life Safety and Stability (2660-9630), 2023)
The article describes the living conditions of an ancient Russian woman, presents biographies of the most famous of them. An assessment of the role of women in the formation and development of Russian statehood and culture is given.